1997
DOI: 10.1111/j.1399-3054.1997.tb00558.x
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose metabolism and fruit growth in parthenocarpic vs seeded blueberry (Vaccinium ashei) fruits

Abstract: Sucrose metabolism and fruit growth in parthenocarpic vs seeded blueberry (Vaccinium ashei) fruits. -Physiol. Plant. 99: 439-446.Although fruit set and development are induced hy applications of gibberellins, final friiit weight of gibberellin-induced parthenocarpic fruit is often less than that of pollinated fruit. We examined changes in the activities of sucrose-metabolizing enzymes and sugar accumulation in developing fruits of cultivated bluebeny (Vaccinium ashei Reade) and their correlation with fruit gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…Other studies, however, have indicated no relationship between sugar content and composition and final fruit size. For example, development of blueberry fruit was not limited by sucrose metabolizing enzyme activity and/or the ability to accumulate sugars (Cano-Medrano and Darnell 1997). Likewise, soybean seed growth was not limited by the endogenous concentration of sucrose in reproductive tissues (Schussler et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies, however, have indicated no relationship between sugar content and composition and final fruit size. For example, development of blueberry fruit was not limited by sucrose metabolizing enzyme activity and/or the ability to accumulate sugars (Cano-Medrano and Darnell 1997). Likewise, soybean seed growth was not limited by the endogenous concentration of sucrose in reproductive tissues (Schussler et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Indicator letters in common denote a lack of a significant difference kinds of fruits. Cano-Medrano and Darnell (1997) found that seeded blueberry fruits needed considerably more carbon supply (calculating respiration and increase of dry weight) for their development than parthenocarpic fruits induced by gibberellin. The process of seed development requires substantial amounts of carbon and energy (Ruan and others 2012).…”
Section: Transcript Accumulation Of Ugpase and Sps Genesmentioning
confidence: 98%
“…The only work on enzymatic characterization of sugar biosynthesis in other berry species studied the relationships between gibberellic acid (GA 3 )-induced parthenocarpy and sugar metabolism in blueberry (Vaccinium ashei). By studying the activity of VaSAIV, VaSPS and VaSS, the authors revealed no limitation on fruit growth by sugar biosynthesis enzymes in either GA 3 -treated parthenocarpic (seedless) or control pollinated (seeded) fruits [20]. NAD+-dependent sorbitol dehydrogenase (SDH) and sorbitol-6-phosphate dehydrogenase (S6PDH) are involved in sorbitol metabolism.…”
Section: Sugar and Acid Compositionmentioning
confidence: 99%